2014
DOI: 10.24925/turjaf.v2i1.42-46.53
|View full text |Cite
|
Sign up to set email alerts
|

Patates Üretiminde Üretim-Fiyat İlişkisinin Koyck Yaklaşımı ile Analitik Olarak Değerlendirilmesi (TR 71 Bölgesi Örneği)

Abstract: In this study, the interaction between potato production and its price from 1991 to 2012 was analyzed using Koyck approach, one of the distributed lag econometric models. The amount of potato production can increase or decrease in the current year based on the prices of previous year, as a product that is appropriate for cobweb theorem, one of economic facts. According to the results of Koyck model, it was determined that potato was affected by the prices of maximum two years retrospectively, and that 1.45 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The lag length was found to be 9 years in the study conducted by Çelik (2015) and 4 years in the study conducted by Çobanoğlu (2010). Similarly, in a study conducted by Ağazade (2021), the lag length was found to be 2 years, while in the study conducted by Doğan et al (2014), it was also found to be 2 years. Similarly, in the studies conducted by Mbise (2016) and Turğut et al (2023), the lag length was found to be 2 years.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The lag length was found to be 9 years in the study conducted by Çelik (2015) and 4 years in the study conducted by Çobanoğlu (2010). Similarly, in a study conducted by Ağazade (2021), the lag length was found to be 2 years, while in the study conducted by Doğan et al (2014), it was also found to be 2 years. Similarly, in the studies conducted by Mbise (2016) and Turğut et al (2023), the lag length was found to be 2 years.…”
Section: Resultsmentioning
confidence: 76%
“…When the relevant literature is examined, it is seen that there is very limited research using the Koyck model to determine the relationship between agricultural product prices and the production of agricultural products in Türkiye. Ağazade (2021) investigated the relationship between cotton production and cotton prices, Avcioğlu and Aksoy (2021) examined the relationship between pistachio production and pistachio prices, Berk (2017) studied the relationship between sunflower production and sunflower prices, Çelik (2014) explored the relationship between hazelnut shelled production and hazelnut shelled prices, Çelik (2015) analyzed the relationship between sheep milk production and sheep milk prices, Çobanoğlu (2010) examined the relationship between strawberry production and strawberry prices, Dikmen (2006) investigated the relationship between tobacco production and tobacco prices, Erdal and Erdal (2008) studied the relationship between dry onion production and dry onion prices, Özçelik and Özer (2006) explored the relationship between wheat production and wheat prices, Özsayın (2017) analyzed the relationship between cow milk production and cow milk prices, Doğan et al (2014) examined the relationship between potato production and potato prices, Abdikoğlu and Unakıtan (2014) investigated the relationship between watermelon production and watermelon prices and Arısoy and Bayramoğlu (2017) attempted to determine the relationship between potato production and potato prices using the Koyck model.…”
Section: Introductionmentioning
confidence: 99%
“…The Koyck model was developed to predict distributed lag models in order to eliminate the problems of multicollinearity and decreasing degrees of freedom depending on the lag length (Koyck, 1954). As a matter of fact, in many studies conducted in different countries, it is seen that the Koyck model is used in the analysis of the relationship between the production quantity and price of different crops (Yurdakul, 1998;Dikmen 2006;Erdal, 2006;Erdal & Erdal, 2008;Çetinkaya, 2012;Çelik, 2014;De Silva et al, 2014;Doğan et al, 2014;Hasan & Khalequzzaman, 2015;Mbise, 2016;Akgül & Yıldız, 2016;Al-Shamary & Mikhlef, 2017;Berk, 2017;Hasan et al, 2017;Ağazade, 2021;Avcıoğlu & Aksoy, 2021;Faied & Elshater, 2022;Turğut et al, 2023).…”
Section: Introductionmentioning
confidence: 99%